Antibiotic resistance in Escherichia coli from Animals, Food and Humans - Elma Hrustemović; Faruk Čaklovica; Jasmina Đeđibegović; Kenan Čaklovica (Indonesian Center for Animal Research and Development, 2022)
Antibiotic resistance is considered a global public health problem and is related to the problem of resistance of bacteria in human and veterinary medicine that are transmitted directly and through the food chain. Uncontrolled use of antibiotics in veterinary practice is a special danger for the development of antibiotic resistance. The problem of public health, human and veterinary is the acquired resistance of bacteria to antibiotics. Of particular importance is the emergence of multidrug resistance to Escherichia coli, which is becoming more common in the world, both in human and veterinary medicine, and the possible transmission of resistant Escherichia coli between animals and humans. The purpose of this paper is to show the importance of the rational use of antibiotics in animals and humans to prevent the spread of antibiotic resistance. Escherichia coli is an intestinal bacterium of all mammals, widespread in the environment and often present in food of animal origin. Today, a pluripotent bacterium and a carrier of antibiotic resistance genes due to anthropogenic factors, and genes are transmitted through animal bacteria, food bacteria to bacteria of human origin.